Flozins - modern treatment for patients with type 2 diabetes - Dominik Augustyn; Krzysztof Pawlikowski; Michał Korpalski; Marek Żygłowicz; Mateusz Marciniak; Adam Torbicki; Piotr Gaworek; Maria Pawluczyk; Alicja Trybuła (Quality in Sport, 2025)
Introduction: